Funciones y estrategias fundamentales de la guía-tutela entre iguales en las primeras edades - J. D. Vargas Cano; L. Villares Bermejo (Universidad de La Rioja, 2013)
In this work we displayed a theoretical frame on the peer guide-tutoring in the early ages. From a pluridimensional perspective we described its main characteristics, in contrast to the adult-child guide. We detailed the main patterns of organization of the guide and, finally, we made specific the characteristics of an effective position of a tutoring in these ages.